Crash of COVID -19 on the Indian Foreign Investments - Malik, Aarti Ohri (Gyan Management Journal, 2022)
Corona viruses are Zoometric that means which are transmitted between animals and humans. Corona virus (COV) is a large family of viruses and COVID -19 is one of them that cause respiratory diseases arraign from the general cold to more stern diseases. COVID -19 that crippled the world economy in the terms of trade and commerce, employment, education and health. The only mechanism that drags out any sick economy from any crisis is its foreign investments. Foreign investments play an important role for the emerging and developing economies in booming their economies through the sources of international finance and portfolio investments. But this time FDI which is already seeing downcast with lower rate of returns will not act as a lubricant for the suffering economies. Uncertainties about the upcoming course and consequence of COVID-19 has made the financial market additional unpredictable, leading to huge collide and wealth wearing away which consecutively impacting consumption level. According to the Department for Promotion of Industry and Internal Trade, on 18th April 2020 the government of India had made certain changes in the foreign Investment policies to encourage opportunistic takeovers and acquisitions.This paper is entirely committed to bring out whether there is a significant impact of the COVID-19 on the Indian foreign investments. For such analyses, the monthly data have been taken for Net Foreign Direct Investments, Foreign Direct Investments by India, Net Portfolio Investments, FII, Portfolio Investments by India and Foreign Investment Inflows. The analysis is then extended in examining the impact of COVID -19 on Market Capitalization (BSE and NSE) and Market Turnover (BSE and NSE). For such analysis T- test and Mann-Whitney Test has been applied.
Keywords: Net Foreign Investments; Foreign Portfolio Investments; Market Turnover and Market Capitalization